Corruption Risks in Smart City Initiatives in Indonesia: Analysis of Legal Framework Adequacy - Alhakim, Abdurrakhman; Sari, Ratna Kumala; Febriyani, Emiliya; Jaya, Febri; Nurlaily, Nurlaily (Kosmik Hukum, 2025)
As sustainability needs continue to gather attention worldwide, the development of smart cities raises novel issues that need to be anticipated, particularly in the line of anti-corruption. This paper explores this novel topic, particularly regarding the emerging risks associated corruption risks around smart city initiatives in Indonesia, by identifying the legal implications of smart city initiatives. It focuses on the inadequacies within the current legal framework, employing the normative legal research method and statutory approach to conduct an analysis of the relevant legal frameworks. Smart city projects promise innovation and better public services. The associated risks identified by the analysis include compromised procurement processes, substandard technologies, and breaches of relevant rights, which instead erode sustainability aspects of Indonesian society, ultimately defeating the purposes of smart city-related initiatives. The anti-corruption legal framework in Indonesia is also found in the analysis to be inadequate in addressing this issue. Therefore, this study proposes a model of legal reforms consisting of key normative aspects that can be considered for future legal development, to enhance oversight and transparency in smart city initiatives, while also ensuring quality results and protecting the public interest.